Zad 1
Rozwiąż równie
a) 3x-5=4+2x
b)-5x+10=-2x-8
c) -5x-17=-9x+3
d)7x+14=5x-22
e) 2x-4+5x=x+2
f) -3+2x-6=3-4x
g)7x+2=5+3x+9
h) -5x+12+x=2x-12

Zad 2
Rozwiąż równania
a) 2(x-3)+3(4-x)=5
b)3(x-4)-2(2x-5)=-4
c)2(x+4)-5(x+3)=2
d) -2(x+3)+4(2x+3)= -6

Zad 3
Rozwiąż równania
a) (4-2x)-(x+3)=(x-5)+(-3-x)
b) (3-2x)+(3x+4)= -(3-2x)+(5x+4)
c) -(x+3)+(2x-1)=(1+4x)+(3+x)
d) -(x+3)-(2x+8)=(-3-2x)+(2x+1)

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T22:07:16+01:00
Zad 1

a) 3x-5=4+2x
3x-2x = 4+5
x = 9

b)-5x+10=-2x-8
-5x+2x = -8-10
-3x = -18 / : (-3)
x = 6

c) -5x-17=-9x+3
-5x+9x = 3+17
4x = 20 / : 4
x=5

d)7x+14=5x-22
7x-5x = -22-14
2x = -36 / : 2
x = -18

e) 2x-4+5x=x+2
2x+5x-x = 2+4
6x = 6 / :6
x = 1

f) -3+2x-6=3-4x
2x+4x = 3+6+3
6x=12 / :6
x = 2

g)7x+2=5+3x+9
7x-3x = 5+9-2
4x = 12 / :4
x = 3

h) -5x+12+x=2-12
-5x+x = 2-12-12
-4x = -22 / : (-4)
x = 5,5

Zad 2

a) 2(x-3)+3(4-x)=5
2x-6+12-3x=5
2x-3x = 5+6-12
-x = -1 / :(-1)
x=1

b)3(x-4)-2(2x-5)=-4
3x-12-4x+10 = -4
3x-4x = -4+12-10
-x = -2 / :(-1)
x = 2

c)2(x+4)-5(x+3)=2
2x+8-5x-15 = 2
2x-5x = 2-8+15
-3x = 9 / : (-3)
x= -3

d) -2(x+3)+4(2x+3)= -6
-2x-6+8x+12 = -6
-2x+8x = -6+6-12
6x = -12 / : 6
x = -2

Zad 3

a) (4-2x)-(x+3)=(x-5)+(-3-x)
4-2x-x-3 = x-5-3-x
-2x-x-x+x = -5-3-4+3
-3x = -9 / : (-3)
x= 3

b) (3-2x)+(3x+4)= -(3-2x)+(5x+4)
3-2x+3x+4 = -3+2x+5x+4
-2x+3x-2x-5x = -3+4-3-4
-6x = -6 / :(-6)
x = 2

c) -(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1 = 1+4x+3+x
-x+2x-4x-x = 1+3+3+1
-4x = 8 / :(-4)
x = -2

d) -(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8 = -3-2x+2x+1
-x-2x+2x-2x = -3+1+3+8
-3x = 9 / :(-3)
x = -3
2010-03-02T22:12:23+01:00
Zad 1.
a) 3x-5=4+2x
3x-2x=4+5
x=9

b)-5x+10=-2x-8
-5x+2x=-10-8
-3x=-18/(-3)
x=6

c)-5x-17=-9x+3
-5x+9x=17+3
4x=20/4
x=5

d)7x+14=5x-22
7x-5x=-22-14
2x=-36/2
x=-18

e)2x-4+5x=x+2
2x+5x-x=2+4
6x=6/6
x=1

f)-3+2x-6=3-4x
2x+4x=3+6+3
6x=12/6
x=2

h) -5x+12+x=2-12
-5x+x=2-12-12
-4x=2/(-4)
x=-0,5

g)7x+2=5+3x+9
7x-3x=5-2+9
4x=12/4
x=3


zad2
a) 2(x-3)+3(4-x)=5
2x-6+12-3x=5
2x-3x=5-12+6
-x=-1/(-1)
x=1

b)3(x-4)-2(2x-5)=-4
3x-12-4x+10=4
3x-4x=4-10+12
-x=-6/(-1)
x=6


c)2(x+4)-5(x+3)=2
2x+8-5x-15=2
2x-5x=2+15-8
-3x=9/(-3)
x=-3

d) -2(x+3)+4(2x+3)= -6
-2x-6+8x+12=-6
-2x+8x=-6+6-12
6x=12/6
x=2

zad 3.
a) (4-2x)-(x+3)=(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
-2x-x-x+x=-4+3-5
-3x=-6/(-3)
x=2

b) (3-2x)+(3x+4)= -(3-2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
-2x+3x-2x-5x=-3+4-3-4
-6x=0
x=0

c) -(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
-x+2x-4x-x=1+3+3+1
-4x=8/(-4)
x=-2

d) -(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8=-3-2x+2x+1
-x-2x+2x-2x=-3+1+3+8
-3x=9/(-3)
x=-3
2010-03-02T22:44:38+01:00
Zadanie 1
a) 3x-5=4+2x
3x-2x=4+5
x=9
b) -5x+10=-2x-8
-5x+2x=-8-10
-3x=-18/*(-1)
3x=18/:3
x=6
c) -5x-17=-9c+3
-5x+9x=3+17
4x=20/:4
x=5
d) 7x+14=5x-22
7x-5x=-22-14
2x=-36/:2
x=-18
e) 2x-4+5x=x+2
2x+5x-x=2+4
7x-x=6
6x=6/:6
x=1
f) -3+2x-6=3-4x
2x+4x=3+3+6
6x=12/:6
x=2
g) 7x+2=5+3x+9
7x-3x=5+9-2
4x=12/:4
x=3
h) -5x+12+x=2x-12
-5x+x-2x=-12-12+5
-7+x=-24+5
-6x=19/*(-1)
6x=19/:6
x=3 i jedna szusta
Zad 2
a)
2(x-3)+3(4-x)=5
2x-6+12-3x=5
2x-3x=5+6-12
-x=-1/*(-1)
x=1
b)
3(x-4)-2(2x-5)=-4
3x-12-4x+5=-4
3x-4x=-4+12-5
-x=3/*(-1)
x=3
c)
2(x+4)-5(x+3)=2
2x+8-5x-15=2
2x-5x=2+15-8
-3x=9/*(-1)
3x=-9/:3
x=3
d)
-2(x+3)+4(2x+3)= -6
-2x-6+8x+12=-6
-2x+8=-6+6-12
8x=-12/:8
x=1 i cztery usme